"The power of Twitter": Using social media at a conference with nursing students. (September 2018) - Jackson, Jennifer; Gettings, Sheryl; Metcalfe, Alison
Abstract: The potential impact of social media use in nursing education, continuing professional development, and nurses' advocacy is unfolding at a rapid pace. Nurse educators are uniquely placed to incorporate the use of social media to enhance students' learning experiences and support students to develop competency in the use of social media for patient benefit. This paper outlines a novel way in which professional education on social media use was integrated into an undergraduate nursing programme. Digital professionalism was cultivated together with collaborative active learning. Students connected using the Twitter hashtag #kclciat18 registered for the 'Connecting it all Together 2017' conference held at the Florence Nightingale Faculty of Nursing, Midwifery & Palliative Care, King's College London . Students were invited to participate in an education session on social media, and live activities using Twitter. The conference provided students with a forum to learn about Twitter and practice using Twitter in a professional capacity. Utilising the healthcare conference hashtag repository, Symplur, quantitative and qualitative measures were accessible indicating the reach and extent of connectivity. A combination of qualitative and quantitative outcome measures will help student nurses appreciate the power of Twitter for patient benefit.